THE IMPORTANCE OF ORAL HEALTH BEHAVIOUR OF CHILDREN FOR THEIR ORAL HEALTH - Anđelić Ivana; Matijević Snežana; Anđelić Jasminka (Sanamed, 2015)
Introduction. Caries or tooth decay regardless of the good knowledge of the nature of the disease and the possibility of its effective prevention is still the most widespread disease in our population. It also very often threatens the functions of organs and even the entire organism. Health culture is an integral part of general culture and health education plays an important role in maintaining health of individuals.